Persuasion and Terror: the Language of Hygiene in Brazilian Schoolbooks (São Paulo, 1920-1950) - Pimenta Rocha, Heloísa (Historia y Memoria de la Educación, 2015)
This article delves into the presence and role played by emotions in schoolbooks dealing with themes related to hygiene and health. To do so, we examine a corpus of textbooks produced between 1920 and 1950, designed for, among others, children attending elementary schools in the state of São Paulo, Brazil. The article focuses, more specifically, on the analysis of the language used in these books, trying to capture the affective dimension present in the treatment of themes such as cleanliness, eating habits, diseases and prevention methods, both for problems concerning the physical body and those considered to be of a moral dimension. An analysis of the textbooks reveals that their contents are meant to convey information about health in an emotional way, where in the name of science and logic, an effort is made to encourage readers to guard themselves against diseases and their consequences. An examination of the language used for dealing with these themes shows us to what degree an affective approach was taken with regard to hygiene and health issues. A strong appeal was made to the emotions in procuring adherence to a healthy, civilized and morally accepted lifestyle, one that could be achieved through the children’s internalization of the prescribed behavior agenda.